Hubungan antara Paparan Iklan Makanan dan Minuman Ringan di Televisi dengan Perilaku Pemilihan Jajanan pada Anak (The Correlation between the Exposure of Advertisement about Snacks and Soft drinks on Television with Children’s Behavior Taking Snacks - Eriga Agustiningsasi; Mury Ririanty; Denny Antyo Hartanto (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Overnutrition status occurs when the intake of food is in excess of daily’s dietary energy. It can make overwight or obesity. One of the factors about it is the media, commercial advertising of snacks and soft drink. The purpose of this study was to analyze the correlation between the exposure of snacks and soft drinks on television with the children’s behavior taking snacks. This study was held at Jember Lor 01’s Elementary School of children with overnutrition status. This study used quantitative analitical and used cross sectional approach. The population of this study were as many as 300 students.The samples of this study were taken by simple random sampling technique in class of 4, 5, and 6. Data were collected by researcher to 82 respondents. The research analysis used Chi Square test at 95% significance level (α = 0.05), but the data not qualify chi-square test. So, this test was replaced with Fisher Exact test. The analysis showed that there was no correlation between the exposure of advertisement about snacks and soft drinks on television with the children’s behavior taking snacks in elementary school of Jember Lor 01 Patrang Distric of Jember. Keywords: overnutrition, behaviour taking snacks